Identification of a recurrent transforming UBR5–ZNF423 fusion gene in EBV‐associated nasopharyngeal carcinoma. Issue 2 (10th September 2013) - Chung, Grace TY; Lung, Raymond WM; Hui, Angela BY; Yip, Kevin YL; Woo, John KS; Chow, Chit; Tong, Carol YK; Lee, Sau‐Dan; Yuen, Jessie WF; Lun, Samantha WM; Tso, Ken KY; Wong, Nathalie; et al.
Abstract Nasopharyngeal carcinoma (NPC) is a distinct type of head and neck cancer which is prevalent in southern China, south‐east Asia and northern Africa. The development and stepwise progression of NPC involves accumulation of multiple gross genetic changes during the clonal expansion of Epstein–Barr virus (EBV)‐infected nasopharyngeal epithelial cell population. Here, using paired‐end whole‐transcriptome sequencing, we discovered a number of chimeric fusion transcripts in a panel of EBV‐positive tumour lines. Among these transcripts, a novel fusion of ubiquitin protein ligase E3 component n‐recognin 5 (UBR5) on 8q22.3 and zinc finger protein 423 (ZNF423) on 16q12.1, identified from the NPC cell line C666‐1, was recurrently detected in 12/144 (8.3%) of primary tumours. The fusion gene contains exon 1 of UBR5 and exons 7–9 of ZNF423 and produces a 94 amino acid chimeric protein including the original C‐terminal EBF binding domain (ZF29‐30) of ZNF423. Notably, the growth of NPC cells with UBR5–ZNF423 rearrangement is dependent on expression of this fusion protein. Knock‐down of UBR5–ZNF423 by fusion‐specific siRNA significantly inhibited the cell proliferation and colony‐forming ability of C666‐1 cells. The transforming ability of UBR5–ZNF423 fusion was also confirmed in NIH3T3 fibroblasts. Constitutive expression of UBR5–ZNF423 in NIH3T3 fibroblasts significantly enhanced its anchorage‐independent growth in soft agar and induced tumour formation in a nude mouse model. These findings suggest that expression of UBR5–ZNF423 protein might contribute to the transformation of a subset of NPCs, possibly by altering the activity of EBFs (early B cell factors). Identification of the oncogenic UBR5–ZNF423 provides new potential opportunities for therapeutic intervention in NPC. © 2013 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.